Source mechanisms and induced seismicity in the Val d'Agri Basin (Italy). Issue 3 (11th April 2023) - Roselli, P; Improta, L; Kwiatek, G; Martínez-Garzón, P; Saccorotti, G; Lombardi, A M
SUMMARY: We present the results from a fully unconstrained moment tensor inversion of induced seismic events in a complex and high seismic hazard region (Val d'Agri basin, Southern Italy). The study area hosts two well-documented cases of induced microseismicity linked to (i) a wastewater injection well of a giant oilfield (the largest in onshore Europe), and (ii) severe seasonal level changes of an artificial lake. In order to gather information on the non-double-couple components of the source and to better understand the rupture mechanisms, we analyse seismic events recorded during daily injection tests in the disposal well. The computed moment tensors have significant non-double-couple components that correlate with the well-head injection pressure. The injection parameters strongly influence the rupture mechanism that can be interpreted as due to the opening/closing of a fracture network inside a fault zone of a pre-existing thrust fault. For the case of the reservoir-induced seismicity, no direct correlations are observed with the loading/unloading of the reservoir.